Selective biostimulation of cold‐ and salt‐tolerant hydrocarbon‐degrading Dietzia maris in petroleum‐contaminated sub‐Arctic soils with high salinity. Issue 1 (30th September 2017) - Chang, Wonjae; Akbari, Ali; David, Carolyn A; Ghoshal, Subhasis
Abstract: BACKGROUND: The dual tolerance of hydrocarbon‐degrading bacteria to low temperatures and salinity has not been extensively reported. This study identifies cold‐ and salt‐tolerant hydrocarbon degraders obtained from petroleum‐contaminated sub‐Arctic soils, with the objective of stimulating target populations and assessing hydrocarbon biodegradation in soils abruptly impacted by salinity. RESULTS: Halotolerant Dietzia and Arthrobacter bacteria were isolated from the soils. Dietzia maris strain NWWC4 can grow in the absence and presence of NaCl (≤12.5% w/v), adheres to hydrocarbons, and produces biosurfactant. The nutrient conditions preferred by strain NWWC4 were characterized to stimulate halotolerant hydrocarbon degraders related to strain NWWC4. In soil‐slurry microcosms with the selected nutrient, Terminal Restriction Fragment Length Polymorphism indicated the dominance of alkB ‐gene‐harboring NWWC4 relatives. Radiolabeled 14 C‐hexadecane mineralization in high‐salinity soil‐slurry microcosms (29 ± 0.33% 14 CO2 production) was strikingly comparable with that in non‐saline conditions (35 ± 0.84% 14 CO2 production). In nutrient‐amended, Arctic‐diesel‐spiked soil microcosms subjected to dual stresses (10 °C and 5% NaCl, w/v), hydrocarbon removal in the diesel range (C10–C21) was 21 ± 8% after 18 days and was comparable with the removal achieved under non‐saline conditions (37 ± 6% removal). CONCLUSION: This study reports the unique versatility of cold‐adapted and salt‐tolerant Dietzia maris capable of degrading hydrocarbons in highly saline and non‐saline conditions. © 2017 Society of Chemical Industry